Pendidikan Digital: Kunci Membuka Pintu Gerbang Masa Depan yang Tidak Terkunci Algoritma - Fitriyana Fitriyana; Elvyani Nuri Harlawati Gaffar; Rizki Nurliana Astuti (FKIP, Universitas Palangka Raya, 2026)
Development of digital technology has brought very big change in the world of education especially in the teaching and learning process which is then expected to become more flexible, interactive and easy to access. but in reality digitalization progress also creates challenges in the form of the influence of algorithms low digital literacy and use Artificial Intelligence (AI) which is excessive in the learning process. Community Service Activities (PKM) carried out in order celebration National Education Day (Hardiknas) with a theme Digital Education; Key Opens the Gate Future Unlocked Algorithm. Activities are carried out and implemented via a webinar held and broadcast live via the Islamic Center of East Kalimantan YouTube channel on May 5, 2026. Methods of implementing activities using guided interactive discussions by a moderator and presenting competent speakers in their fields. Results of the discussion shows that technology is increasingly developing able to provide convenience in the process learning and increasing understanding participant regarding the importance of digital education, digital literacy influence of algorithms and usage Artificial Intelligence (AI) wiser in teaching and learning activities.